2008
DOI: 10.1016/j.tet.2008.09.058
|View full text |Cite
|
Sign up to set email alerts
|

Amino acids as selective acylating agents: regioselective N1-acylation of imidazolidin-4-one derivatives of the antimalarial drug primaquine

Abstract: a b s t r a c tThe acylation of bioactive primaquine-based imidazolidin-4-ones was studied using N a -Boc-protected glycine as acylating agent. Two synthesis routes, eight different coupling methods and seven distinct solvents were compared. Mild carbodiimide-based couplings on high dielectric constant solvents such as DMF or MeCN increased acylation yields, whereas alcohols inhibited carbodiimide-mediated acylations to take place. Achievement of the synthetic goals was limited by the size of the imidazolidin-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 27 publications
0
23
0
Order By: Relevance
“…Briefly, once prepared as previously described,29 imidazolidin-4-one precursors 4 were coupled to N α -Boc-protected amino acids (BocAAOH) by means of a carbodiimide (diisopropylcarbodiimide, DIC) as condensation agent, in the presence of 1-hydroxybenzotriazole (HOBt) as auxiliary nucleophile. Boc was then removed from the condensation product by acidolysis with trifluoroacetic acid (TFA), yielding the target compounds 5 in good yields and with correct spectroscopic data.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Briefly, once prepared as previously described,29 imidazolidin-4-one precursors 4 were coupled to N α -Boc-protected amino acids (BocAAOH) by means of a carbodiimide (diisopropylcarbodiimide, DIC) as condensation agent, in the presence of 1-hydroxybenzotriazole (HOBt) as auxiliary nucleophile. Boc was then removed from the condensation product by acidolysis with trifluoroacetic acid (TFA), yielding the target compounds 5 in good yields and with correct spectroscopic data.…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, our previous work has shown that R 1 substituents on imidazolidin-4-ones 4 (i) should be small (H, Me) for higher transmission blocking activities,2 and (ii) do not have a marked influence on compounds activity against both blood-stage P. falciparum or P. carinii 28. Bulky substituents on the imidazolidin-4-one’s C-2 carbon are also detrimental towards N -acylation, so only propanone-derived imidazolidin-4-ones are efficiently N -acylated 29. Nevertheless, insertion of larger substituents on the imidazolidin-4-one’s C-2, as those previously reported by us,26,28 would probably lead to a decreased water-solubility of final compounds 5 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The relevance of such a group has been proposed earlier 33 and confirmed by our previous studies with PQ peptide and peptidomimetic (imidazoquine) derivatives. [23][24][25][26][27][28][29][30][31] To check this hypothesis, we are now working on the synthesis and in vitro evaluation of second-generation primacenes bearing basic amino groups.…”
Section: 31mentioning
confidence: 99%